Supporting surgeons in patient-centred complex decision-making: a qualitative analysis of the impact of a perioperative physician clinic. Issue 12 (23rd December 2019) - Pham, Clarabelle T; Gibb, Catherine L; Fitridge, Robert A; Karnon, Jon; Hoon, Elizabeth
Abstract : Objective: Patients with comorbidities can be referred to a physician-led high-risk clinic for medical optimisation prior to elective surgery at the discretion of the surgical consultant, but the factors that influence this referral are not well understood. The aims of this study were to understand the factors that influence a surgeon's decision to refer a patient to the clinic, and how the clinic impacts on the management of complex patients. Design: Qualitative study using theoretical thematic analysis to analyse transcribed semi-structured interviews. Setting: Interviews were held in either the surgical consultant's private office or a quiet office/room in the hospital ward. Participants: Seven surgical consultants who were eligible to refer patients to the clinic. Results: When discussing the factors that influence a referral to the clinic, all participants initially described the optimisation of comorbidities and would then discuss with examples the challenges with managing complex patients and communicating the risks involved with having surgery. When discussing the role of the clinic, two related subthemes were dominant and focused on the management of risk in complex patients. The participants valued the involvement of the clinic in the decision-making and communication of risks to the patient. Conclusions: The integration of the high-risk clinic in this study appears to offer additional value in supporting the decision-making process for the surgical team and patient beyond the clinical outcomes. The factors that influence a surgeon's decision to refer a patient to the clinic appear to be driven by the aim to manage the uncertainty and risk to the patient regarding surgery and it was seen as a strategy for managing difficult and complex cases.